2012
DOI: 10.1128/jcm.06503-11
|View full text |Cite
|
Sign up to set email alerts
|

Strong Correlation between Liver and Serum Levels of Hepatitis C Virus Core Antigen and RNA in Chronically Infected Patients

Abstract: HCV core antigen (Ag) and HCV RNA levels were evaluated in matched liver biopsy samples and sera from 22 patients with hepatitis C infection by using the quantitative Architect HCV Ag immunoassay and a real-time RT-qPCR assay, respectively. The data showed a strong correlation between liver and serum compartments of HCV Ag levels (r ‫؍‬ 0.80) and HCV RNA levels (r ‫؍‬ 0.87). In summary, the serum HCV Ag and RNA levels reflect the intrahepatic values. Hepatitis C virus (HCV) is an important human pathogen; worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
(27 reference statements)
3
19
3
Order By: Relevance
“…Several other studies using HCVcAg testing reported a significant correlation between serum levels of HCV-RNA and HCVcAg with different linear regression coefficients ranging from 0.6 to 0.8 (22,24,36,30−33), which is higher than seen in our study. In addition, the weak correlation reported in our study is lower than that reported elsewhere among those infected with HCV genotype 4 or other genotypes (9)(10)(11)34,35). This could be attributed to viral genetic differences and/or patient characteristics.…”
Section: Discussioncontrasting
confidence: 55%
“…Several other studies using HCVcAg testing reported a significant correlation between serum levels of HCV-RNA and HCVcAg with different linear regression coefficients ranging from 0.6 to 0.8 (22,24,36,30−33), which is higher than seen in our study. In addition, the weak correlation reported in our study is lower than that reported elsewhere among those infected with HCV genotype 4 or other genotypes (9)(10)(11)34,35). This could be attributed to viral genetic differences and/or patient characteristics.…”
Section: Discussioncontrasting
confidence: 55%
“…The ten remaining studies did not have data to calculate specificity (11, 38, 4143, 50, 53, 57, 61, 63) and were only included in the univariate pooled sensitivity estimate. For the bivariate analysis there were 12,670 total samples.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent data have demonstrated that serum HCVcAg concentrations correlate well with HCV RNA levels in HCV monoinfected patients [6,7,8,9,10,11,12]. In the present study, we further investigated the use of HCVcAg measurement in HCV/HIV coinfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated good correlation between HCVcAg and HCV RNA levels, particularly in HCV-monoinfected individuals [6,7,8,9,10,11,12,13]. As a result, HCVcAg testing is considered to be an alternative assay to conventional HCV RNA quantification with the advantages of rapidity, reproducibility and feasibility in settings with limited resources [14].…”
Section: Introductionmentioning
confidence: 99%